The persistence of antimicrobial resistance and related environmental factors in abandoned and working swine feedlots. (December 2019) - Li, Na; Zhu, Changxiong; Liu, Chong; Zhang, Ximei; Ding, Junjun; Zandi, Peiman; Li, Hongna
Abstract: Swine feedlots that have operated in the absence of adequate disposal facilities are being demolished under the new environmental protection policies in China. The environmental behavior and transmission risks of antimicrobial resistance genes (ARGs) are unclear for these abandoned swine feedlots. We examined 40 soil samples that originated from the soils adjacent to two abandoned and two working swine feedlots to explore: 1) the distribution patterns and vertical transmission of 17 ARGs and two integron genes and 2) the bacterial community as well as their correlation with environmental factors and target genes. We found that seven and nine out of forty-eight subtypes of veterinary antimicrobials (VAs) were detected in the soil near abandoned feedlots and working feedlots, respectively. Three tet genes ( tetM, tetO and tetW) were particularly enriched in the soil adjacent to both abandoned and working feedlots. The tetM gene was a "hub" on the network of the topsoil. The relative abundance of Firmicutes ranged from 2.5 to 9% in the soil near two Beijing feedlots and was significantly higher than that in the upstream blank control (CK soil) (ANOVA, p < 0.05). Overall, the ARG distribution patterns in the soils adjacent to abandoned swine feedlots were similar to the working feedlots. This study offers basic information on the prevalence and transmission risk of ARGs in abandoned swine feedlots and provides a reference for the restoration and reuse of demolished feedlots. Graphical abstract: Image 1 Highlights: VAs could be detected in adjacent soil after swine feedlots was demolished for one year. ARGs were prevalent in soil near abandoned feedlots like the working ones. Abundance of ARGs was not significantly different between topsoil and subsoil soil. Co-occurrence of ARGs and bacteria was most intense in topsoil of working feedlots. Firmicutes were more enriched in soil near swine feedlots. Abstract : Persistence of ARGs in the adjacent soil was observed after the feedlots being demolished for one year and the ARG transmission risk should be monitored.